Incorporação de pó de traquito em massa cerâmica para produção de blocos de vedação - Paz, Francisca Irleide Lima (2020)
This research sought to analyze the influence of incorporating trachyte rock waste on the production of ceramic sealing bricks. This influence was considered because the alkalinity of this type of rock, given by the concentration of the feldspar mineral in its composition, promotes the melting action. For the preparation of the specimens, the trachyte waste was collected in São Gonçalo do Amarante-CE and was used clay soil from Russas-CE. The clay soil and the trachyte waste were submitted to the physical, chemical and mineralogical characterization, through X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD), and the clay soil was also submitted to plasticity and moisture content test went. After the preparation of the specimens according to the proposed methodology, they were submitted to the linear retraction, water absorption and resistance to the uniaxial compression test. As of the results obtained in the technological tests carried out with the specimens, the incorporation of 5% in trachyte waste in the ceramic mass for the production of ceramic sealing bricks was considered satisfactory, favoring up to 50°C the reduction of the temperature necessary to carry out the burning of them, without loss of resistance, deformation or increase in water absorption.